Makna Konotatif pada Penamaan Tokoh “Malin Kundang” dalam Cerita Rakyat Minangkabau (Pusat riset dan Inovasi Nasional, 2026)
This research is driven by the significance of examining language meaning, particularly connotative meaning which is often used to convey implicit messages in literary works. Folktales, as one type of oral literature, often utilize character names that carry specific meanings, such as Malin Kundang from Minangkabau. The aim of this research is to uncover the connotative meaning of the character name “Malin Kundang”, as well as its relationship with the moral and cultural values of the society. The methodology involves qualitative research using semantic analysis and a descriptive approach. Data were collected from the Malin Kundang folktale text thru library study and documentation techniques. Next, the processes of identification, classification, and interpretation of meaning were done in order to examine the data. The research result show that denotatively, the name Malin Kundang only functions as the identity of the character, but connotatively, it functions as a symbol of a disobedient child who does not respect their parents. The meaning is formed from the plot of the story and reinforced by the Minangkabau cultural values that uphold respect for parents. The implications of this research indicate that the naming of characters in folklore is not only linguistic but also reflects the moral and cultural values inherited by society.